Exploring the Impact of ACE Inhibition in Immunity and Disease - Oosthuizen, Delia; Sturrock, Edward D. (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Angiotensin-converting enzyme (ACE) is a zinc-dependent dipeptidyl carboxypeptidase and is crucial in the renin-angiotensin-aldosterone system (RAAS) but also implicated in immune regulation. Intrinsic ACE has been detected in several immune cell populations, including macrophages and neutrophils, where its overexpression results in enhanced bactericidal and antitumour responses, independent of angiotensin II. With roles in antigen presentation and inflammation, the impact of ACE inhibitors must be explored to understand how ACE inhibition may impact our ability to clear infections or malignancy, particularly in the wake of the coronavirus (SARS-CoV2) pandemic and as antibiotic resistance grows. Patients using ACE inhibitors may be more at risk of postsurgical complications as ACE inhibition in human neutrophils results in decreased ROS and phagocytosis whilst angiotensin receptor blockers (ARBs) have no effect. In contrast, ACE is also elevated in certain autoimmune diseases such as rheumatoid arthritis and lupus, and its inhibition benefits patient outcome where inflammatory immune cells are overactive. Although the ACE autoimmune landscape is changing, some studies have conflicting results and require further input. This review seeks to highlight the need for further research covering ACE inhibitor therapeutics and their potential role in improving autoimmune conditions, cancer, or how they may contribute to immunocompromise during infection and neurodegenerative diseases. Understanding ACE inhibition in immune cells is a developing field that will alter how ACE inhibitors are designed in future and aid in developing therapeutic interventions.